HUBUNGAN FAKTOR MATERNAL DENGAN BERAT BAYI LAHIR DI WILAYAH KERJA UPTD PUSKESMAS KARANGAMPEL KABUPATEN INDRAMAYU - Sutrisno; Endah Sari Purbanisngsih; Citra Setyo Dwi Andhini (LPPM ITEKES Mahardika, 2018)
Background:Neonates are newborn babies, aged 0-28 days.Low birth weight (LBW) is one of the main factors in increasing mortality, neonatal morbidity and disability. Purpose: This study aims to determine the relationship between maternal factors and the weight of babies bornin the work area of ​​the Karangampel Community Health Center, Indramayu Regency. Method:This research method uses descriptive analytic, using a quantitative approach and cross sectional design.The population is all mothers who have given birth in the work area of ​​the Karangampel Community Health Center, Indramayu Regency,the data was obtained from the book records of patients at the Poned UPTD Karangampel Public Health Center, Indramayu Regencyas many as 175 respondents and sampling using Randon Sampling technique obtained 64 respondents.The instrument used in the form of observation sheets, as well as data analysis using the chi square test. Result:The results of the study using chi square statistical test showed that the relationship between maternal factors (maternal age) and birth weight obtained results of p-value = 0.011, the relationship of maternal factors (maternal parity) with birth weight obtained results of p-value = 0.802, while the relationship factor maternal (pregnancy distance) with birth weight obtained results of p-value = 0.019. Of the three categories of maternal factors, maternal factors (maternal age and gestational distance) were <α = 0.05, and maternal factors (parity)> α = 0.05. Conclusion:We hope this research can be used as reading material and study materials for students and teachers about the study between maternal factors and birth weight.